Multi-gradient positive electrode and preparation method thereof, and all-solid-state battery and preparation method thereof

By designing a multi-gradient structure in the positive electrode of solid-state lithium batteries, adjusting the content of conductive agents and solid electrolytes, and building electronic channels and ion channels, the problems of low ion diffusion efficiency and increased contact resistance in solid-state lithium batteries are solved, and a higher level of 的循环稳定性和容量保持率。

CN119400802AActive Publication Date: 2025-02-07SUZHOU QINGTAO NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202411564314.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-07
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

In solid-state lithium batteries, the rigidity of the solid-solid contact interface limits the diffusion efficiency of ions, and the contact resistance increases during the charge and discharge cycle, affecting electron transmission, resulting in fast attenuation of the battery capacity and poor circulation stability.

Method used

Design a multi-gradient positive electrode, including current collector, high electron channel layer and high ion channel layer, and adjust the content ratio of conductive agent and solid electrolyte to form a gradient of conductive agent and solid electrolyte component, build electronic channels and ion channels, and optimize electrodes performance.

Benefits of technology

It improves the electronic transmission rate and ion transmission rate of solid-state batteries, takes into account energy density and rate performance, and extends the cycling stability and capacity retention rate of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400802A_ABST
    Figure CN119400802A_ABST
Patent Text Reader

Abstract

The invention relates to a multi-gradient positive electrode and a preparation method thereof, and an all-solid-state battery and a preparation method thereof. Wherein the multi-gradient positive electrode comprises a current collector, a high electron channel layer and a high ion channel layer which are arranged in sequence, and the mass ratios of positive electrode active materials in the high electron channel layer and the high ion channel layer are the same; the mass ratio of the conductive agent in the high electron channel layer is higher than the mass ratio of the conductive agent in the high ion channel layer; and the mass ratio of the solid electrolyte in the high electron channel layer is lower than the mass ratio of the solid electrolyte in the high ion channel layer. The mass ratio of the positive electrode active material in the positive electrode is kept, and the component gradient of the electrode is constructed through the content change of the conductive agent and the solid electrolyte, so that the optimized distribution of the electrode components is realized, the contact between the solid electrolyte and the active material is increased, and the high energy density is kept; therefore, the solid battery gives consideration to both energy density and rate capability, and the cycling stability and the capacity retention ratio of the solid battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a multi-gradient positive electrode and a preparation method thereof, an all-solid-state battery and a preparation method thereof. Background Art

[0002] Solid-state lithium batteries are used in many fields, and high energy density and power density are the core performance indicators of solid-state lithium batteries. However, in the design of solid-state lithium batteries, the solid-solid contact interface between the solid electrolyte and the electrode is rigid, which limits the diffusion efficiency of ions. At the same time, during the charge and discharge cycle, due to chemical reactions, the contact resistance between the current collector and the electrode material may increase, resulting in an increase in the interface impedance, which affects the electron transmission. The impact of the above factors on the transmission of ions and electrons further leads to problems such as rapid battery capacity decay and poor cycle stability. However, if the content of electrode active materials is reduced in order to increase the transmission rate of ions and electrons, it will inevitably affect the energy density of the battery. If the amount of electrode active materials is increased, the plate resistance increases and the capacity is significantly reduced. Therefore, how to balance high energy density, power density and cycle has always been a technical challenge. Summary of the invention

[0003] Based on this, the present application provides a multi-gradient positive electrode and a preparation method thereof, an all-solid-state battery and a preparation method thereof, to solve the above-mentioned technical problems.

[0004] The first aspect of the present application provides a multi-gradient positive electrode, comprising a current collector, a high electron channel layer and a high ion channel layer arranged in sequence, wherein the mass proportion of the positive electrode active material in the high electron channel layer and the high ion channel layer is the same;

[0005] The mass proportion of the conductive agent in the high electron channel layer is higher than the mass proportion of the conductive agent in the high ion channel layer;

[0006] The mass proportion of the solid electrolyte in the high electron channel layer is lower than the mass proportion of the solid electrolyte in the high ion channel layer.

[0007] In some embodiments, the mass proportion of the conductive agent in the high electron channel layer is 2% to 5%, and the mass proportion of the solid electrolyte is 10% to 15%.

[0008] In some embodiments, the mass proportion of the conductive agent in the high ion channel layer is 1% to 3%, and the mass proportion of the solid electrolyte is 14% to 20%.

[0009] In some embodiments, the high electron channel layer has a thickness of 15 μm to 40 μm.

[0010] In some embodiments, the high ion channel layer has a thickness of 15 μm to 40 μm.

[0011] The second aspect of the present application provides a method for preparing the multi-gradient positive electrode provided in the first aspect, comprising the following steps:

[0012] S1, mixing the positive electrode active material, the conductive agent, the binder and the solid electrolyte by air jet milling to obtain a first mixed material;

[0013] S2, coating the first mixed material on the surface of the current collector to form a high electron channel layer on the surface of the current collector;

[0014] S3, mixing the positive electrode active material, the conductive agent, the binder and the solid electrolyte by air jet milling to obtain a second mixed material;

[0015] S4, coating the second mixed material on the surface of the high electron channel layer to form a high ion channel layer on the surface of the high electron channel layer;

[0016] S5. Roll-pressing treatment to produce a multi-gradient positive electrode.

[0017] In some embodiments, the coating is performed in step S2 and step S4 by dry spraying or electrostatic spraying.

[0018] In some embodiments, the binder is polytetrafluoroethylene.

[0019] The third aspect of the present application provides an all-solid-state battery, which includes the multi-gradient positive electrode provided by the first aspect above or the multi-gradient positive electrode prepared by the preparation method provided by the second aspect above.

[0020] The fourth aspect of the present application provides a method for preparing the all-solid-state battery provided in the third aspect, comprising the following steps:

[0021] A solid electrolyte mixture consisting of a solid electrolyte and a binder is applied to the surface of a high ion channel in a multi-gradient positive electrode to form a solid electrolyte film on the surface of the high ion channel;

[0022] The multi-gradient cathode and solid electrolyte membrane were roll-pressed.

[0023] In this application, the positive electrode of the solid battery is set to be composed of two layers of film layers with different component gradients, and the component gradient of the two layers of film is realized by changing the content ratio of the conductive agent and the solid electrolyte, so as to optimize the electrode performance. Among them, the high electron channel layer is close to the current collector, and the high ion channel layer is close to the solid electrolyte. The conductive agent content of the high electron channel layer accounts for a higher proportion than the high ion channel layer, forming a conductive agent composition gradient, constructing an electron channel, which is beneficial to the electron transmission on the current collector side and reducing its cross-sectional interface impedance. The solid electrolyte content of the high ion channel layer accounts for a higher proportion than the high electron channel layer, forming a solid electrolyte composition gradient, constructing an ion channel, and facilitating ion transmission. Without changing the mass proportion of the positive electrode active material in the positive electrode sheet, the composition gradient of the electrode is constructed by changing the content of the conductive agent and the solid electrolyte, and the optimized distribution of the electrode components is realized, which can not only increase the contact between the solid electrolyte and the active material, but also maintain a high energy density, so that the solid battery takes into account both energy density and rate performance, and improves the cycle stability and capacity retention rate of the solid battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] FIG1 is a flow chart of a method for preparing a multi-gradient positive electrode in one embodiment of the present application. DETAILED DESCRIPTION

[0025] References to embodiments of the present application will now be provided in detail, one or more embodiments of which are described below. Each embodiment is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0026] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0027] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0028] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0029] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 100~150 nm means that the units of the left endpoint "100" and the right endpoint "150" are both nm (nanometers).

[0030] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0031] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0032] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, mentioning that the method may also include step (c) means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0033] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0034] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0035] During the development of all-solid-state batteries, the positive and negative electrodes adopted the design of traditional lithium-ion liquid batteries, replacing the liquid electrolyte with a solid electrolyte layer. In this structure, the electrolyte between the electrodes is essentially compressed to the thickness of the solid electrolyte layer, resulting in uneven distribution of the electrolyte between the thicker electrode plates. It becomes difficult for the electrolyte to penetrate to the bottom of the electrode, thereby limiting the capacity of the battery.

[0036] In traditional technology, solid-state batteries are improved by adding solid electrolytes to electrodes to form ion channels. However, this design will increase the resistance of the electrode plates when the active material loading is increased, which will significantly reduce the energy storage capacity of the battery; at the same time, it will affect the proportion of solid electrolytes and conductive agents, thus affecting the overall performance of the battery.

[0037] In addition, it is well known that lithium battery pole pieces generally have two competing charge transfer processes that determine the electrical performance: on the one hand, ion transfer in the electrolyte; on the other hand, electron transfer connected by the active materials and conductive agents of the electrode itself. Regardless of the discharge or charging process, at the current collector, the electron current density is the largest, while the ion current density is 0; at the interface of the middle diaphragm, the electron current density is 0, while the ion current density is the largest. Therefore, electrodes with high porosity exhibit good ion transfer properties, but poor electronic conductivity; while highly dense electrodes exhibit poor ion transfer properties, but have good electronic conductivity. In traditional technology, liquid batteries achieve both rate and energy density through the construction of pole pieces with multi-pore gradients; however, in all-solid-state batteries, solid electrolytes are generally required to be filled in the gaps to form ion channels, so there is no so-called pore gradient.

[0038] Therefore, how to provide a solid battery that takes into account energy density, rate performance and cycle performance has become a technical problem that needs to be solved urgently.

[0039] In response to the above technical problems, the first aspect of the present application provides a multi-gradient positive electrode, including a current collector, a high electron channel layer and a high ion channel layer arranged in sequence, wherein the mass proportions of the positive electrode active material in the high electron channel layer and the high ion channel layer are the same; the mass proportion of the conductive agent in the high electron channel layer is higher than the mass proportion of the conductive agent in the high ion channel layer; the mass proportion of the solid electrolyte in the high electron channel layer is lower than the mass proportion of the solid electrolyte in the high ion channel layer.

[0040] In some embodiments, the mass proportion of the conductive agent in the high electron channel layer is 2% to 5%, including but not limited to 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 5%.

[0041] In some embodiments, the mass proportion of the solid electrolyte in the high electron channel layer is 10% to 15%, including but not limited to 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 14%, and 15%.

[0042] In some embodiments, the mass proportion of the conductive agent in the high ion channel layer is 1% to 3%, including but not limited to 1%, 1.5%, 2%, 2.5%, and 3%.

[0043] In some embodiments, the mass proportion of the solid electrolyte in the high ion channel layer is 14% to 20%, including but not limited to 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, and 20%.

[0044] In some embodiments, the thickness of the high electron channel layer is 15 μm to 40 μm, including but not limited to 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, and 40 μm.

[0045] In some embodiments, the thickness of the high ion channel layer is 15 μm to 40 μm, including but not limited to 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, and 40 μm.

[0046] This application adjusts the content of the conductive agent and solid electrolyte in the pole piece according to the distribution law of ion and electron current density to form a multi-gradient pole piece structure of electron channels and ion channels. By setting the positive electrode of the solid battery to be composed of two layers of film layers with different component gradients, the component gradient of the two layers of film is achieved by changing the content ratio of the conductive agent and the solid electrolyte, and the electrode performance is optimized. Among them, the high electron channel layer is close to the current collector, and the high ion channel layer is close to the solid electrolyte. The conductive agent content of the high electron channel layer accounts for a higher proportion than the high ion channel layer, forming a conductive agent component gradient, constructing an electron channel, facilitating electron transmission on the current collector side, and reducing its cross-sectional interface impedance. The solid electrolyte content of the high ion channel layer accounts for a higher proportion than the high electron channel layer, forming a solid electrolyte component gradient, constructing an ion channel, and facilitating ion transmission. Without changing the mass proportion of the positive electrode active material in the positive electrode sheet, the composition gradient of the electrode is constructed by changing the content of the conductive agent and the solid electrolyte to achieve an optimized distribution of the electrode components. This not only increases the contact between the solid electrolyte and the active material, but also maintains a high energy density, allowing the solid battery to take into account both energy density and rate performance, thereby improving the cycle stability and capacity retention rate of the solid battery.

[0047] As shown in FIG. 1 , the second aspect of the present application provides a method for preparing a multi-gradient positive electrode as provided in the first aspect above, comprising the following steps:

[0048] S1, mixing the positive electrode active material, the conductive agent, the binder and the solid electrolyte by air jet milling to obtain a first mixed material;

[0049] S2, coating the first mixed material on the surface of the current collector to form a high electron channel layer on the surface of the current collector;

[0050] S3, mixing the positive electrode active material, the conductive agent, the binder and the solid electrolyte by air jet milling to obtain a second mixed material;

[0051] S4, coating the second mixed material on the surface of the high electron channel layer to form a high ion channel layer on the surface of the high electron channel layer;

[0052] S5. Roll-pressing treatment to produce a multi-gradient positive electrode.

[0053] The positive electrode active material in the multi-gradient positive electrode can be any material that can be used as a positive electrode active material for a lithium-ion secondary battery, without any limitation on its use. For example, the positive electrode active material may include layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or compounds substituted by one or more transition metals; Li 1+x Mn 2-x Lithium manganese oxides such as LiMnO4 (x is 0~0.33), LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, Cu2V2O7; molecular formula LiNi 1-x M X Lithium nickel oxide represented by O2 (wherein M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, including at least one of the above elements, wherein x is 0.01-0.3); molecular formula LiMn 2-x M x O2 (wherein M is Co, Ni, Fe, Cr, Zn or Ta and x is 0.01~0.1) or Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu or Zn) lithium manganese composite oxide; LiNi x Mn 2-x O4 is a spinel lithium manganese composite oxide; the Li part in the LiMn2O4 formula is replaced by alkaline earth metal ions; LiNi x Co y Mn (1-x-y) O2 (where x=0.8, y=0.1); disulfide; Fe2(MoO4)3; lithium cobalt oxide; lithium iron phosphate; elemental sulfur (S8); Li2S n (n=1), organic sulfur compounds or carbon sulfur polymers (C2S x) n (x is 2.5 ~ 50, n is 2); may include sulfur compounds, etc.

[0054] The conductive agent in the multi-gradient positive electrode is not particularly limited as long as it has conductivity without causing chemical changes in the all-solid battery, including but not limited to graphites such as natural graphite and artificial graphite; conductive carbon black (Super-P), acetylene black, Ketjen black, channel black, furnace black, lamp black, summer black, etc. Conductive fibers, such as carbon fibers and metal fibers, such as VGCF (vapor-grown carbon fibers); metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; it may include one or a mixture of two or more selected from conductive materials such as polyphenylene derivatives.

[0055] The binder in the multi-gradient positive electrode is polytetrafluoroethylene (PTFE) and related derivatives.

[0056] The solid electrolyte material in the multi-gradient positive electrode may be a halide, however, other known materials such as a sulfide-based solid electrolyte material, a polymer-based solid electrolyte, and an oxide-based solid electrolyte material may be used as the solid electrolyte material depending on the design.

[0057] In some embodiments, the coating is performed in step S2 and step S4 by dry spraying or electrostatic spraying.

[0058] In some embodiments, the binder is polytetrafluoroethylene (PTFE).

[0059] In the present application, the positive electrode active material, the conductive agent, the binder and the solid electrolyte are mixed by air flow milling, so that the polytetrafluoroethylene (PTFE) is fibrillated and then bonded to the positive electrode active material, the conductive agent and the solid electrolyte. No solvent is required, which is more environmentally friendly.

[0060] In the present application, the roller pressing process in step S5 makes the current collector, the high electron channel layer and the high ion channel layer fit more closely; at the same time, the porosity of the high electron channel layer and the high ion channel layer is reduced.

[0061] The third aspect of the present application provides an all-solid-state battery, which includes the multi-gradient positive electrode provided by the first aspect above or the multi-gradient positive electrode prepared by the preparation method provided by the second aspect above.

[0062] The fourth aspect of the present application provides a method for preparing the all-solid-state battery provided in the third aspect, comprising the following steps:

[0063] A solid electrolyte mixture consisting of a solid electrolyte and a binder is applied to the surface of a high ion channel in a multi-gradient positive electrode to form a solid electrolyte film on the surface of the high ion channel;

[0064] The multi-gradient cathode and solid electrolyte membrane were roll-pressed.

[0065] In some embodiments, the method for preparing an all-solid-state battery further comprises the following steps:

[0066] The multi-gradient positive electrode, solid electrolyte membrane and negative electrode sheet that have been roller-pressed are stacked in sequence and assembled under pressure to produce an all-solid-state battery.

[0067] It can be understood that in the present application, there is no particular limitation on the process of assembling the positive and negative electrode sheets and the solid electrolyte membrane. Any known assembly method can be used in the present application without violating the inventive concept of the present application.

[0068] The present application will be further described below with reference to specific embodiments and comparative examples.

[0069] Example 1

[0070] The positive electrode active material NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2), conductive agent Super-P, binder PTFE and solid electrolyte Li3InCl6 are mixed by air flow milling to make PTFE fibrillate and then bond the positive electrode active material, conductive agent and solid electrolyte to obtain the first mixture.

[0071] The first mixed material is coated on the surface of the current collector by dry spraying to form a high electron channel layer on the surface of the current collector. The thickness of the high electron channel layer is 30 μm.

[0072] The positive electrode active material NCM811, the conductive agent Super-P, the binder PTFE and the solid electrolyte Li3InCl6 in a mass ratio of 80:2:2:16 are mixed by air flow milling to make the PTFE fibrillate and then bond the positive electrode active material, the conductive agent and the solid electrolyte to obtain a second mixture.

[0073] The second mixed material is coated on the surface of the high electron channel layer by dry spraying to form a high ion channel layer on the surface of the high electron channel layer. The thickness of the high ion channel layer is 30 μm.

[0074] The porosity is reduced by roller pressing to produce a multi-gradient positive electrode.

[0075] Example 2

[0076] The positive electrode active material NCM811, the conductive agent Super-P, the binder PTFE and the solid electrolyte Li3InCl6 in a mass ratio of 80:4:2:14 are mixed by air flow milling to make the PTFE fibrillate and then bond the positive electrode active material, the conductive agent and the solid electrolyte to obtain a first mixture.

[0077] The first mixed material is coated on the surface of the current collector by dry spraying to form a high electron channel layer on the surface of the current collector. The thickness of the high electron channel layer is 30 μm.

[0078] The positive electrode active material NCM811, the conductive agent Super-P, the binder PTFE and the solid electrolyte Li3InCl6 in a mass ratio of 80:2:2:16 are mixed by air flow milling to make the PTFE fibrillate and then bond the positive electrode active material, the conductive agent and the solid electrolyte to obtain a second mixture.

[0079] The second mixed material is coated on the surface of the high electron channel layer by dry spraying to form a high ion channel layer on the surface of the high electron channel layer. The thickness of the high ion channel layer is 30 μm.

[0080] The porosity is reduced by roller pressing to produce a multi-gradient positive electrode.

[0081] Example 3

[0082] The positive electrode active material NCM811, the conductive agent Super-P, the binder PTFE and the solid electrolyte Li3InCl6 in a mass ratio of 80:3:2:15 are mixed by air flow milling to make the PTFE fibrillate and then bond the positive electrode active material, the conductive agent and the solid electrolyte to obtain a first mixture.

[0083] The first mixed material is coated on the surface of the current collector by dry spraying to form a high electron channel layer on the surface of the current collector. The thickness of the high electron channel layer is 30 μm.

[0084] The positive electrode active material NCM811, the conductive agent Super-P, the binder PTFE and the solid electrolyte Li3InCl6 in a mass ratio of 80:1:2:17 are mixed by air flow milling to make the PTFE fibrillate and then bond the positive electrode active material, the conductive agent and the solid electrolyte to obtain a second mixture.

[0085] The second mixed material is coated on the surface of the high electron channel layer by dry spraying to form a high ion channel layer on the surface of the high electron channel layer. The thickness of the high ion channel layer is 30 μm.

[0086] The porosity is reduced by roller pressing to produce a multi-gradient positive electrode.

[0087] Example 4

[0088] The positive electrode active material NCM811, the conductive agent Super-P, the binder PTFE and the solid electrolyte Li3InCl6 in a mass ratio of 78:5:2:15 are mixed by air flow milling to make the PTFE fibrillate and then bond the positive electrode active material, the conductive agent and the solid electrolyte to obtain a first mixture.

[0089] The first mixed material is coated on the surface of the current collector by electrostatic spraying to form a high electron channel layer on the surface of the current collector. The thickness of the high electron channel layer is 30 μm.

[0090] The positive electrode active material NCM811, the conductive agent Super-P, the binder PTFE and the solid electrolyte Li3InCl6 in a mass ratio of 78:2:2:18 are mixed by air flow milling to make the PTFE fibrillate and then bond the positive electrode active material, the conductive agent and the solid electrolyte to obtain a second mixture.

[0091] The second mixed material is coated on the surface of the high electron channel layer by dry spraying to form a high ion channel layer on the surface of the high electron channel layer. The thickness of the high ion channel layer is 30 μm.

[0092] The porosity is reduced by roller pressing to produce a multi-gradient positive electrode.

[0093] Comparative Example 1

[0094] The positive electrode active material NCM811, the conductive agent Super-P, the binder PTFE and the solid electrolyte Li3InCl6 in a mass ratio of 80:2:2:16 are mixed by air flow milling to make the PTFE fibrillate and then bond the positive electrode active material, the conductive agent and the solid electrolyte to obtain a first mixture.

[0095] The first mixed material is coated on the surface of the current collector by dry spraying, and the thickness of the first coating layer is 30 μm.

[0096] The positive electrode active material NCM811, the conductive agent Super-P, the binder PTFE and the solid electrolyte Li3InCl6 in a mass ratio of 80:5:2:13 are mixed by air flow milling to make the PTFE fibrillate and then bond the positive electrode active material, the conductive agent and the solid electrolyte to obtain a second mixture.

[0097] The second mixed material is coated on the surface of the first coating layer by dry spraying to form a second coating layer with a thickness of 30 μm.

[0098] The porosity is reduced by roller pressing to produce a multi-gradient positive electrode.

[0099] Comparative Example 2

[0100] The positive electrode active material NCM811, the conductive agent Super-P, the binder PTFE and the solid electrolyte Li3InCl6 in a mass ratio of 80:5:2:13 were mixed by air flow milling to make the PTFE fibrillate and then bond the positive electrode active material, the conductive agent and the solid electrolyte to obtain a mixture, which was coated on the surface of the current collector by dry spraying, and the porosity was reduced by roller pressing to obtain a positive electrode.

[0101] Comparative Example 3

[0102] The positive electrode active material NCM811, the conductive agent Super-P, the binder PTFE and the solid electrolyte Li3InCl6 in a mass ratio of 83:2:2:13 are mixed by air flow milling to make the PTFE fibrillate and then bond the positive electrode active material, the conductive agent and the solid electrolyte to obtain a first mixture.

[0103] The positive electrode active material NCM811, the conductive agent Super-P, the binder PTFE and the solid electrolyte Li3InCl6 in a mass ratio of 80:2:2:16 are mixed by air flow milling to make the PTFE fibrillate and then bond the positive electrode active material, the conductive agent and the solid electrolyte to obtain a second mixture.

[0104] The first mixed material and the second mixed material are sequentially coated on the surface of the current collector by dry spraying, and the porosity is reduced by roller pressing to obtain a positive electrode.

[0105] Comparative Example 4

[0106] The positive electrode active material NCM811, the conductive agent Super-P, the binder PTFE and the solid electrolyte Li3InCl6 in a mass ratio of 78:5:2:15 are mixed by air flow milling to make the PTFE fibrillate and then bond the positive electrode active material, the conductive agent and the solid electrolyte to obtain a first mixture.

[0107] The positive electrode active material NCM811, the conductive agent Super-P, the binder PTFE and the solid electrolyte Li3InCl6 in a mass ratio of 81:2:2:15 are mixed by air flow milling to make the PTFE fibrillate and then bond the positive electrode active material, the conductive agent and the solid electrolyte to obtain a second mixture.

[0108] The first mixed material and the second mixed material are sequentially coated on the surface of the current collector by dry spraying, and the porosity is reduced by roller pressing to obtain a positive electrode.

[0109] Preparation of all-solid-state batteries:

[0110] A solid electrolyte mixture prepared from a binder PTFE and a solid electrolyte Li3InCl6 in a mass ratio of 5:95 is applied to the surface of the positive electrode prepared in the above embodiments and comparative examples, and the porosity is reduced by rolling to complete the preparation of the solid electrolyte membrane. The positive electrode, solid electrolyte membrane and metal lithium sheet that have been rolled are stacked in sequence, pressurized and assembled to obtain an all-solid-state battery. The 3C discharge capacity retention rate and 100 cycle retention rate are tested. The test parameters of the embodiments and comparative examples are summarized in Table 1 below:

[0111] Table 1

[0112] 100-cycle cycle retention rate 3C discharge capacity retention rate Example 1 90% 95% Example 2 89% 94% Example 3 88% 93% Example 4 91% 94% Comparative Example 1 74% 87% Comparative Example 2 80% 91% Comparative Example 3 77% 88% Comparative Example 4 85% 90%

[0113] The technical solution adopted in this application improves the electron transfer rate and ion transfer rate of the all-solid-state battery, so the rate performance of the battery is better. And the experimental results show that the 3C discharge capacity retention rate and 100-cycle cycle retention rate of the battery in the embodiment are significantly improved compared with the comparative example, so the cycle stability and capacity retention rate of the solid battery are enhanced.

[0114] In the technical solution adopted in the present application, the mass proportion of the positive electrode active material in the positive electrode remains unchanged. Therefore, compared with the technical solution of realizing the electrode gradient design by changing the content of the active material and the solid electrolyte, the present application has a higher energy density.

[0115] The preparation of the multi-gradient positive electrode provided in the present application is simpler, the process flow is simplified, the manufacturing cost is lower, and it is more adaptable to the large-scale batch production of solid-state batteries.

[0116] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0117] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A multi-gradient positive electrode, characterized in that: It includes a current collector, a high electron channel layer and a high ion channel layer arranged in sequence, wherein the mass proportion of the positive electrode active material in the high electron channel layer and the high ion channel layer is the same; The mass proportion of the conductive agent in the high electron channel layer is higher than the mass proportion of the conductive agent in the high ion channel layer; The mass proportion of the solid electrolyte in the high electron channel layer is lower than the mass proportion of the solid electrolyte in the high ion channel layer.

2. The multi-gradient positive electrode according to claim 1, characterized in that The mass proportion of the conductive agent in the high electron channel layer is 2% to 5%, and the mass proportion of the solid electrolyte is 10% to 15%.

3. The multi-gradient positive electrode according to claim 1, characterized in that: The mass proportion of the conductive agent in the high ion channel layer is 1% to 3%, and the mass proportion of the solid electrolyte is 14% to 20%.

4. The multi-gradient positive electrode according to claim 1, characterized in that The thickness of the high electron channel layer is 15 μm to 40 μm.

5. The multi-gradient positive electrode according to claim 1, characterized in that: The thickness of the high ion channel layer is 15 μm to 40 μm.

6. A method for preparing a multi-gradient positive electrode as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S1, mixing the positive electrode active material, the conductive agent, the binder and the solid electrolyte by air jet milling to obtain a first mixed material; S2, coating the first mixed material on the surface of the current collector to form a high electron channel layer on the surface of the current collector; S3, mixing the positive electrode active material, the conductive agent, the binder and the solid electrolyte by air jet milling to obtain a second mixed material; S4, coating the second mixed material on the surface of the high electron channel layer to form a high ion channel layer on the surface of the high electron channel layer; S5. Roll-pressing treatment to produce a multi-gradient positive electrode.

7. The preparation method according to claim 6, characterized in that: In step S2 and step S4, coating is performed by dry spraying or electrostatic spraying.

8. The preparation method according to claim 6, characterized in that: The binder is polytetrafluoroethylene.

9. An all-solid-state battery, characterized in that: The all-solid-state battery comprises the multi-gradient positive electrode according to any one of claims 1 to 5 or the multi-gradient positive electrode prepared by the preparation method according to any one of claims 6 to 8.

10. A method for preparing an all-solid-state battery as claimed in claim 9, characterized in that: The following steps are involved: Applying a solid electrolyte mixture consisting of a solid electrolyte and a binder to the surface of a high ion channel in a multi-gradient positive electrode to form a solid electrolyte membrane on the surface of the high ion channel; The multi-gradient cathode and the solid electrolyte membrane are subjected to a roll pressing process.

Citation Information

Patent Citations

  • Multifunctional composite positive electrode sheet for rechargeable and dischargeable solid battery, preparation method and secondary battery

    CN111326708A

  • Pole piece, preparation method of pole piece, battery, battery module, battery pack and device

    CN117352651A

  • All-solid-state battery and manufacturing method

    CN117712503A

  • Multi-layer all-solid-state battery and preparation method and application thereof

    CN117996218A

  • All-solid-state double-layer composite positive electrode, preparation method thereof and lithium ion battery

    CN118198335A

Cited By

  • All-solid-state battery and three-dimensional interface construction method of all-solid-state battery and application thereof

    CN122843528A